Prognostic Impact of Mitral Regurgitation Before and After Transcatheter Aortic Valve Replacement in Patients With Severe Low‐Flow, Low‐Gradient Aortic Stenosis - Germano Junior Ferruzzi; Angelo Silverio; Arturo Giordano; Nicola Corcione; Michele Bellino; Tiziana Attisano; Cesare Baldi; Alberto Morello; Giuseppe Biondi‐Zoccai; Rodolfo Citro; Carmine Vecchione; Gennaro Galasso (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background There is little evidence about the prognostic role of mitral regurgitation (MR) in patients with low‐flow, low‐gradient aortic stenosis undergoing transcatheter aortic valve replacement (TAVR). The aim of this study was to assess the prevalence and outcome implications of MR severity in patients with low‐flow, low‐gradient aortic stenosis undergoing TAVR, and to evaluate whether MR improvement after TAVR could influence clinical outcome. Methods and Results This study included consecutive patients with low‐flow, low‐gradient aortic stenosis undergoing TAVR at 2 Italian high‐volume centers. The study population was categorized according to the baseline MR severity and to the presence of MR improvement at discharge. The primary outcome was the composite of all‐cause death and hospitalization for worsening heart failure up to 1 year. The study included 268 patients; 57 (21%) patients showed MR >2+. Patients with MR >2+ showed a lower 1‐year survival free from the primary outcome (P<0.001), all‐cause death (P<0.001), and heart failure hospitalization (P<0.001) compared with patients with MR ≤2+. At multivariable analysis, baseline MR >2+ was an independent predictor of the primary outcome (P<0.001). Among patients with baseline MR >2+, MR improvement was reported in 24 (44%) cases after TAVR. The persistence of MR was associated with a significantly reduced survival free from the primary outcome, all‐cause death, and heart failure hospitalization up to 1 year. Conclusions In this study, the presence of moderately severe to severe MR in patients with low‐flow, low‐gradient aortic stenosis undergoing TAVR portends a worse clinical outcome at 1 year. TAVR may improve MR severity in nearly half of the patients, resulting in a potential outcome benefit after discharge.